The Effect of Audit Committee, Company Size, and Auditor Reputation on Audit Quality with Audit Fees as an Intervening Variable - Yulia Saftiana; Sulastri Sulastri; Azwardi Azwardi (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to analyze the influences of audit committee, company size, and auditor’s reputation on audit quality with audit fees as an intervening variable. Population of the research is 102 companies in the financial sector listed on the Indonesian stock exchange from 2020 to 2022. Sample was taken by using purposive sampling and 65 companies were obtained as research samples for three years of observation, resulting in a sample of 195 data. The data was analyzed by using multiple regression analysis and path analysis. The result shows that audit committee and auditor’s reputation have no influences to the audit fees, company size has significant effect on audit fees, auditor’s reputation and audit fees have no influences to the audit quality, audit committee and company size have significant effect on audit quality, and audit fees can’t mediate audit committee, company size, and auditor’s reputation on audit quality.